Short-process preparation method of low-yield-ratio double-phase high-entropy alloy

By regulating the proportion and precipitation phase distribution of elements such as Al, Co, Cr, Fe, Ni in the short process preparation method of high entropy alloys, the problem of high yield and strength ratio of existing high entropy alloys is solved, and low cost and low The efficient preparation of Quqiangbi improves tensile strength and the service safety of components.

CN119307799AActive Publication Date: 2025-01-14KUNMING UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411587732.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

There are serious components and tissue segregation in the smelting and preparation process of existing high entropy alloys, which leads to relatively high yield strength and is difficult to meet the demand for component safety in the service environment containing shock and vibration.

Method used

Using the short process preparation method of low yield strength ratio biphasic high entropy alloy, the specific insulation and quenching treatment are carried out by mixing and heating elements such as Al, Co, Cr, Fe, Ni in a muffle furnace, and regulating the phase ratio and precipitation are regulated. The size and distribution of the phases reduce the yield and strength ratio.

Benefits of technology

Achieve efficient and low-yield dual-phase high-entropy alloys, which significantly improve tensile strength, reduce yield strength, shorten production cycles, improve the impact and vibration performance of components, and enhance service reliability and safety. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307799A_ABST
    Figure CN119307799A_ABST
Patent Text Reader

Abstract

The invention discloses a short-process preparation method of a low-yield-ratio double-phase high-entropy alloy, which comprises the following steps: smelting prepared alloy elements to obtain a double-phase high-entropy alloy cast ingot, heating and insulating the double-phase high-entropy alloy cast ingot, and then quenching to obtain the low-yield-ratio double-phase high-entropy alloy. One-step heat treatment is adopted, the tensile strength of the biphase high-entropy alloy cast ingot is further improved, meanwhile, the yield strength of the biphase high-entropy alloy cast ingot is reduced, the yield ratio of the biphase high-entropy alloy is effectively reduced, and compared with a rolling annealing treatment or multi-stage heat treatment process, the method has the advantages of being short in process, high in efficiency and low in cost and is suitable for industrial application and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy preparation, and in particular to a short-process preparation method of a low-yield ratio dual-phase high-entropy alloy. Background Art

[0002] High entropy alloys reduce the tendency of intermediate phase formation and improve the stability of simple solid solution phases by rationally designing the composition and proportion of multiple main elements. Their unique microstructural characteristics and the "high entropy effect", "hysteresis diffusion effect", "lattice distortion effect" and "cocktail effect" give them excellent mechanical properties, such as high hardness, high strength, high temperature resistance, corrosion resistance, and radiation resistance. They are new high-performance metal structural materials with great application potential. Among them, FCC high entropy alloys have excellent plasticity and fracture toughness, but their strength is usually not as good as that of BCC high entropy alloys; BCC high entropy alloys have high strength, wear resistance and good high temperature stability, but their low elongation is the main factor limiting their application. In order to achieve a good match between strength and plasticity, dual-phase and multi-phase high entropy alloys achieve a significant improvement in comprehensive performance through the synergistic effect of multiple strengthening mechanisms, such as the widely used Al 0.7 CoCrFeNi. In order to reduce costs, arc melting, induction melting or suspension melting are usually used to prepare high entropy alloys. However, the multi-principal component composition leads to serious composition and organizational segregation, which in turn affects the performance of high entropy alloys. For example, Al 0.7 The yield strength ratio of CoCrFeNi dual-phase high entropy alloy is usually 60%-70%, which is difficult to meet the requirements of component safety in service environments containing impact and vibration.

[0003] Therefore, while improving the fracture strength of the smelted dual-phase high-entropy alloy, further reducing its yield ratio can achieve a simultaneous improvement in effective buffering capacity and overload resistance, which is of great practical significance for ensuring the safety and reliability of component service. Summary of the invention

[0004] In order to solve the above technical problems, the present invention designs a short-process preparation method of a low yield ratio dual-phase high entropy alloy.

[0005] In order to achieve the above technical effects, the present invention is implemented by the following technical scheme: a short-process preparation method of a low yield ratio dual-phase high entropy alloy, characterized in that it comprises the following steps:

[0006] S1. Prepare Al material, Co material, Cr material, Fe material and Ni material; and weigh each material according to the element type and designed content molar ratio of any alloy shown in the following (1)-(5),

[0007] (1) Al xCoCrFeNi, 0.5≤x≤0.9, the molar ratio of any two elements in the other element contents is 1:1;

[0008] (2) AlCo x CrFeNi, 2.0≤x≤5.0, the molar ratio of any two elements in the other element contents is 1:1;

[0009] (3) AlCoCr x FeNi, x≤1.0, the molar ratio of any two elements in the other element contents is 1:1;

[0010] (4) AlCoCrFe x Ni, 0.2≤x<0.6, the molar ratio of any two elements in the other element contents is 1:1;

[0011] (5) AlCoCrFeNi x , 1.5≤x<3.0, the molar ratio of any two elements in the other element contents is 1:1;

[0012] Then the weighed alloy mixture is placed in a muffle furnace for smelting to obtain a dual-phase high entropy alloy ingot;

[0013] S2, placing the dual-phase high entropy alloy ingot in a resistance furnace and heating it to 600-1300° C. at a heating rate of 2-20° C. / min;

[0014] S3, when the temperature reaches 600-1300° C., the temperature is stopped, and the high entropy alloy ingot is subjected to a heat preservation treatment in a resistance furnace at 600-1300° C. for 0.5-36 hours;

[0015] S4. After the heat preservation treatment, the high entropy alloy ingot is placed in a quenching medium for quenching to obtain CoCrFeNiAl x A series of low yield ratio duplex high entropy alloys.

[0016] Furthermore, the maximum temperature in the resistance furnace during heating is 900-1250°C.

[0017] Furthermore, the heat preservation treatment time is 1 to 3 hours.

[0018] Furthermore, the heating rate of the resistance furnace is 5-10°C / min.

[0019] Furthermore, the smelting adopts one of arc melting, induction melting or suspension melting commonly used in industry.

[0020] Furthermore, the resistance furnace adopts a conventional air resistance furnace or a vacuum resistance furnace.

[0021] Furthermore, the quenching medium is a water-based or oil-based coolant.

[0022] Furthermore, the Al material, Co material, Cr material, Fe material and Ni material are all in the form of blocks, sheets or wires.

[0023] The beneficial effects of the present invention are:

[0024] Compared with the existing rolling annealing process or multi-stage heat treatment process, the preparation method described in the present invention can regulate the phase ratio and the size and distribution of the precipitated phase in one step, does not require vacuum heating, has a short process, and only requires one quenching treatment, which greatly shortens the production cycle, and realizes the preparation of a low yield ratio dual-phase high entropy alloy with high efficiency and low cost, and further improves the tensile strength of the dual-phase high entropy alloy, reduces its yield strength, and effectively reduces the yield ratio. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 For suspension smelting of Al 0.7 Comparison of microstructure and phase content of CoCrFeNi dual-phase high entropy alloy ingot after being heated to 1000°C and kept for 1h and water quenched by the process of the present invention;

[0027] Figure 2 For suspension smelting of Al 0.7 Microstructure and phase content distribution of CoCrFeNi dual-phase high entropy alloy ingot after being heated to 1000°C and kept for 2h and water quenched by the process of the present invention;

[0028] Figure 3 For suspension smelting of Al 0.7 Microstructure and phase content distribution of CoCrFeNi dual-phase high entropy alloy ingot after being heated to 1000°C and kept for 3h and water quenched by the process of the present invention;

[0029] Figure 4 For suspension smelting of Al 0.7 Microstructure and phase content distribution of CoCrFeNi dual-phase high entropy alloy ingot after being heated to 1050°C and kept for 3 hours and water quenched by the process of the present invention;

[0030] Figure 5 For suspension smelting of Al 0.7 Microstructure and phase content distribution of CoCrFeNi dual-phase high entropy alloy ingot after heating to 1150°C and keeping for 3h and water quenching by the process of the present invention;

[0031] Figure 6 For suspension smelting of Al 0.7 Microstructure and phase content distribution of CoCrFeNi dual-phase high entropy alloy ingot after being heated to 1250°C and kept for 3 hours and water quenched by the process of the present invention;

[0032] Figure 7 For suspension smelting of Al 0.7 A comparison diagram of true stress-true stress curves of CoCrFeNi two-phase high entropy alloy ingots and water quenching after heating to different temperatures and holding for different times by the process of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] All embodiments of the present invention are smelting Al 0.7 CoCrFeNi dual-phase high entropy alloy ingot.

[0036] Conventional comparative example: suspension smelting of Al 0.7 CoCrFeNi dual-phase high entropy alloy ingot has a yield strength of 745MPa, a tensile strength of 1115MPa, and a yield strength ratio of 66.8%.

[0037] Example 2

[0038] The short process preparation method of the low yield ratio dual-phase high entropy alloy of the present invention is used to prepare Al 0.7 CoCrFeNi two-phase high entropy alloy, as follows:

[0039] In a conventional muffle furnace, Al is melted 0.7 The CoCrFeNi dual-phase high entropy alloy ingot was heated to 1000°C and kept for 1 hour for water quenching. The vermicular and basket-weave regions in the original cast alloy disappeared, a feather-like structure appeared, and a B2 phase precipitated in the FCC phase. The yield strength was 610MPa, the tensile strength was 1421MPa, and the yield strength ratio dropped to 42.9%. The strength increased by 27.4% and the yield strength ratio decreased by 35.8%.

[0040] Figure 1 Original smelting Al 0.7Comparison of microstructure and phase content of CoCrFeNi dual-phase high entropy alloy ingot after heating at 1000℃ for 1h and water quenching by the process of the present invention. The original structure is a basket-weave structure composed of an FCC phase and a vermicular or noodle-like structure and a BCC / B2 phase, and the FCC phase and BCC phase account for 70.4% and 29.6% respectively. After being kept at 1000℃ for 1h and water quenched, the FCC phase is reduced to 58.3%, the vermicular and basket-weave regions disappear, a feather-like structure appears, and the BCC phase increases to 41.7%. The changes in phase content and phase morphology are Al 0.7 The main reason for the increase in tensile strength and decrease in yield ratio of CoCrFeNi dual-phase high entropy alloy.

[0041] Example 2

[0042] The short process preparation method of the low yield ratio dual-phase high entropy alloy of the present invention is used to prepare Al 0.7 CoCrFeNi two-phase high entropy alloy, as follows:

[0043] In a conventional muffle furnace, Al is melted 0.7 The CoCrFeNi dual-phase high entropy alloy ingot was heated to 1000°C and kept for 2 hours for water quenching. A feather-like structure appeared, and a small amount of B2 phase precipitated in the FCC phase. The alloy yield strength was 664MPa, the tensile strength was 1419MPa, and the yield strength ratio dropped to 46.8%. The strength increased by 27.3% and the yield strength ratio decreased by 30.0%.

[0044] Figure 2 For the original suspension smelting Al 0.7 The microstructure and phase content distribution diagram of the CoCrFeNi two-phase high entropy alloy ingot after being heated at 1000℃ for 2h and water quenched by the process of the present invention. After being water quenched at 1000℃ for 2h, the alloy structure showed that the layered FCC phase and BCC phase were distributed alternately and there was a feather-like structure. Compared with the water quenching treatment at 1000℃ for 1h, the content of B2 precipitate phase in FCC was reduced, but the average size of B2 precipitate phase increased and the average phase spacing decreased. FCC phase and BCC phase accounted for 61.2% and 38.3% respectively. The changes in phase content and morphology, precipitate phase size and average phase spacing are Al 0.7 The main reason for the increase in tensile strength and decrease in yield ratio of CoCrFeNi dual-phase high entropy alloy.

[0045] Example 3

[0046] The short process preparation method of the low yield ratio dual-phase high entropy alloy of the present invention is used to prepare Al 0.7 CoCrFeNi two-phase high entropy alloy, as follows:

[0047] In a conventional muffle furnace, Al is melted 0.7The CoCrFeNi dual-phase high entropy alloy ingot was heated to 1000°C and kept for 3 hours for water quenching. A feather-like structure appeared, and the content of B2 phase precipitated in the FCC phase was further reduced. Its yield strength was 670MPa and its tensile strength was 1426MPa. The strength was increased by 27.9% and the yield strength ratio was reduced to 47.0%.

[0048] Figure 3 Original smelting Al 0.7 The microstructure and phase content distribution diagram of the CoCrFeNi dual-phase high entropy alloy ingot after being heated to 1000℃ and kept for 3 hours by the process of the present invention and water quenched. After being kept at 1000℃ for 3 hours and water quenched, the alloy structure is characterized by the interlaced distribution of layered FCC phase and BCC phase, and feather-like structure still exists. The content of B2 phase precipitated in the FCC phase is slightly less than that when kept for 2 hours, and its average phase size and average phase spacing are slightly increased. The FCC phase and BCC phase account for 62.7% and 37.3% respectively. The phase content and morphology changes are still Al 0.7 The main reason for the increase in tensile strength and decrease in yield strength ratio of CoCrFeNi dual-phase high entropy alloy is that after being kept at 1000℃ for more than 3 hours, the yield strength ratio decreases gradually and becomes stable if the holding time is further extended.

[0049] Example 4

[0050] The short process preparation method of the low yield ratio dual-phase high entropy alloy of the present invention is used to prepare Al 0.7 CoCrFeNi two-phase high entropy alloy, as follows:

[0051] In a conventional muffle furnace, Al is melted 0.7 The CoCrFeNi dual-phase high entropy alloy ingot was heated to 1050°C, kept for 3 hours and water quenched, with a yield strength of 573MPa and a tensile strength of 1358MPa. The strength increased by 21.8% and the yield strength ratio decreased to 42.2%.

[0052] Figure 4 Original smelting Al 0.7 The microstructure and phase content distribution diagram of the CoCrFeNi two-phase high entropy alloy ingot after being heated at 1050℃ for 3 hours and water quenched by the process of the present invention. After being water quenched at 1050℃ for 3 hours, the alloy structure showed a layered FCC phase and BCC phase interlaced, the B2 precipitated phase was basically dissolved and the feather-like structure disappeared, and an obvious spheroidized B2 phase structure appeared. The FCC phase and BCC phase accounted for 63.6% and 36.4%, respectively. Compared with heating at 1000℃ for 3 hours and water quenching, the decrease in the yield strength ratio decreased when the heating temperature increased by 50℃. The phase content and morphology changes are Al 0.7 The main reasons for the increase in tensile strength, decrease in yield ratio and reduction in the decrease in yield ratio are the effects of the CoCrFeNi dual-phase high entropy alloy.

[0053] Example 5

[0054] The short process preparation method of the low yield ratio dual-phase high entropy alloy of the present invention is used to prepare Al 0.7 CoCrFeNi two-phase high entropy alloy, as follows:

[0055] Al is melted in a conventional muffle 0.7 The CoCrFeNi dual-phase high entropy alloy ingot was heated to 1150°C and kept for 3 hours for water quenching. The yield strength of the alloy was 553MPa and the tensile strength was 1308MPa. The strength was increased by 17.3% and the yield strength ratio was reduced to 42.3%.

[0056] Figure 5 Original smelting Al 0.7 The microstructure and phase content distribution diagram of the CoCrFeNi two-phase high entropy alloy ingot after being heated at 1150℃ for 3h and water quenched by the process of the present invention. After being water quenched at 1150℃ for 3h, the alloy structure is characterized by the interlaced distribution of layered FCC phase and BCC phase, the thickness of the two-phase layer is significantly increased, there is no B2 precipitation phase in the FCC phase, the spheroidized structure is significantly increased, and the FCC phase and BCC phase account for 66.7% and 33.3% respectively. Compared with heating at 1050℃ for 3h and water quenching, the yield strength ratio remains stable when the heating temperature is increased by 100℃. The alloy phase content, the spacing between the two-phase layers and the content of spheroidized structure are the main reasons for maintaining the stability of the yield strength ratio.

[0057] Example 6

[0058] The short process preparation method of the low yield ratio dual-phase high entropy alloy of the present invention is used to prepare Al 0.7 CoCrFeNi two-phase high entropy alloy, as follows:

[0059] Al is melted in a conventional muffle 0.7 The CoCrFeNi dual-phase high entropy alloy ingot was heated to 1250°C, kept warm for 3 hours and water quenched, with a yield strength of 475MPa and a tensile strength of 1326MPa. The strength increased by 18.9% and the yield strength ratio decreased to 35.8%.

[0060] Figure 6 Original smelting Al 0.7The microstructure and phase content distribution diagram of the CoCrFeNi two-phase high entropy alloy ingot after being heated at 1250℃ for 3 hours and water quenched by the process of the present invention. After being heated at 1250℃ for 3 hours and water quenched, the alloy structure showed that the layered FCC phase and the BCC phase were distributed alternately, and the thickness of the two phases was further increased. There were spheroidized and massive B2 phase structures in the structure, and the FCC phase and BCC phase accounted for 68.7% and 31.3% respectively. Compared with heating at 1150℃ for 3 hours and water quenching, the yield strength ratio was further reduced when the heating temperature was increased by 100℃, and the alloy phase content, the increase in the spacing between the two phase layers, and the appearance of spheroidized and massive B2 phase structures were Al 0.7 This is the main reason why the yield ratio of CoCrFeNi dual-phase high entropy alloy further decreases.

[0061] Example 7

[0062] like Figure 7 As shown, in Examples 2 to 6, Al was obtained by heating to different temperatures and keeping the temperature for different times within the temperature range of 1000°C to 1250°C and the time range of 1h-3h. 0.7 True stress-strain curve of CoCrFeNi dual-phase high entropy alloy. 0.7 CoCrFeNi dual-phase high entropy alloy ingot, Al prepared by the present invention 0.7 The tensile strength of CoCrFeNi dual-phase high entropy alloy increased by 49.6%-91.4%, the yield strength decreased by 10.0%-36.2%, and the yield strength ratio decreased by 29.6%-46.3%. By rationally controlling the proportion of FCC phase and BCC phase, the interlamellar spacing between the two phases, and the size, morphology and distribution of B2 precipitate phase, Al 0.7 The reduction in the yield ratio and the improvement in tensile strength of the CoCrFeNi dual-phase high-entropy alloy can provide it with effective energy absorption, buffering and shock absorption effects when it is subjected to dynamic loads such as impact, vibration and collision, which is of great practical significance for improving the service reliability and safety of the dual-phase high-entropy alloy.

Claims

1. A short-process preparation method for a low yield ratio dual-phase high entropy alloy, characterized in that: The following steps are involved: S1. Prepare Al material, Co material, Cr material, Fe material and Ni material; and weigh each material according to the element type and designed content molar ratio of any alloy shown in the following (1)-(5), (1) Al x CoCrFeNi, 0.5≤x≤0.9, the molar ratio of any two elements in the other element contents is 1:1; (2) AlCo x CrFeNi, 2.0≤x≤5.0, the molar ratio of any two elements in the other element contents is 1:1; (3) AlCoCr x FeNi, x≤1.0, the molar ratio of any two elements in the other element contents is 1:1; (4) AlCoCrFe x Ni, 0.2≤x<0.6, the molar ratio of any two elements in the other element contents is 1:1; (5) AlCoCrFeNi x , 1.5≤x<3.0, the molar ratio of any two elements in the other element contents is 1:1; Then the weighed alloy mixture is placed in a muffle furnace for smelting to obtain a dual-phase high entropy alloy ingot; S2, placing the dual-phase high entropy alloy ingot in a resistance furnace and heating it to 600-1300° C. at a heating rate of 2-20° C. / min; S3, when the temperature reaches 600-1300° C., the temperature is stopped, and the high entropy alloy ingot is subjected to a heat preservation treatment in a resistance furnace at 600-1300° C. for 0.5-36 hours; S4. After the heat preservation treatment, the high entropy alloy ingot is placed in a quenching medium for quenching to obtain CoCrFeNiAl x A series of low yield ratio duplex high entropy alloys.

2. A short-process preparation method for a low yield ratio dual-phase high entropy alloy according to claim 1, characterized in that: During heating, the maximum temperature in the resistance furnace is 900-1250°C.

3. A short-process preparation method for a low yield ratio dual-phase high entropy alloy according to claim 1, characterized in that: The time of the heat preservation treatment is 1 to 3 hours.

4. A short-process preparation method for a low yield ratio dual-phase high entropy alloy according to claim 1, characterized in that: The heating speed of the resistance furnace is 5-10°C / min.

5. The short-process preparation method of a low yield ratio dual-phase high entropy alloy according to claim 1, characterized in that: The smelting adopts one of arc melting, induction melting or suspension melting commonly used in industry.

6. A short-process preparation method for a low yield ratio dual-phase high entropy alloy according to claim 1, characterized in that: The resistance furnace adopts a conventional air resistance furnace or a vacuum resistance furnace.

7. A short-process preparation method for a low yield ratio dual-phase high entropy alloy according to claim 1, characterized in that: The quenching medium is a water-based or oil-based coolant.

8. A short-process preparation method for a low yield ratio dual-phase high entropy alloy according to claim 1, characterized in that: The Al material, Co material, Cr material, Fe material and Ni material are all in the form of blocks, sheets or wires.

Citation Information

Patent Citations

  • High strength and high hardness AlCoCrFeNi high-entropy alloy and preparation method thereof

    CN107267843A

  • Nb microalloyed Ni-Co-Fe-Cr-Al high-entropy alloy

    CN107739956A

  • High-toughness Cr-Mn-Fe-Ni double-phase high-entropy alloy and preparation method thereof

    CN113106316A

  • Combined AlCoCrFeNi2.1 eutectic high-entropy alloy with ultrahigh strength and plasticity and preparation method thereof

    CN115491565A

  • High-strength gradient structure FeCoNiCr series high-entropy alloy and preparation method thereof

    CN116287928A